2014
DOI: 10.2458/56.16685
|View full text |Cite
|
Sign up to set email alerts
|

High-Precision Bayesian Modeling of Samples Susceptible to Inbuilt Age

Abstract: Radiocarbon dates on samples susceptible to inbuilt age are common in the chronological record of many archaeological and environmental sites. Indeed, fragments of charcoal and wood are sometimes the only materials sufficiently well preserved for dating. However, where high-precision estimates are required the extra uncertainty associated with such measurements often renders them unusable. This article tests three Bayesian modeling approaches that are designed to tackle this problem. The findings of our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 18 publications
0
95
0
1
Order By: Relevance
“…The second method is running a charcoal outlier model (Bronk Ramsey 2009b, Dee andBronk Ramsey 2014). Such a model can allow for outliers due to old wood effect, but still allow the dates to be included in the analysis.…”
Section: Datingmentioning
confidence: 99%
See 1 more Smart Citation
“…The second method is running a charcoal outlier model (Bronk Ramsey 2009b, Dee andBronk Ramsey 2014). Such a model can allow for outliers due to old wood effect, but still allow the dates to be included in the analysis.…”
Section: Datingmentioning
confidence: 99%
“…This method is useful in many situations, but it is questionable if it adds any value to this question, since it is doubtful whether the After function puts enough weight on the possibility that the dates could in fact be contemporary with the event they should date. Testing has shown that the result is often imprecise when dealing with datasets consisting only or mainly of charcoal dates (Dee and Bronk Ramsey 2014).…”
Section: Datingmentioning
confidence: 99%
“…It has been demonstrated in Bayesian models that a small dataset has a greater detrimental impact on chronological resolution than the potential of unidentified charcoals to skew to older ages [29]. Outlier analysis specifically designed to account for this inbuilt age in charcoal is promising [5] [29], but requires additional constraints (e.g., dates on short-lived materials or stratigraphy) against which to anchor the model (see also [30] where the model allows a small number of charcoal samples with inbuilt age to be younger than the context they represent, as would be the case with intrusive material).…”
Section: Comment On Datesmentioning
confidence: 99%
“…Outliers can be handled in one of two ways: elimination or down-weighting (Dee and Bronk Ramsey 2014; Bronk Ramsey 2009b). It is a common practice to simply discard outliers.…”
Section: Analysis Of Datesmentioning
confidence: 99%